2020
DOI: 10.1080/21870764.2020.1834912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of porous hydroxyapatite synthesized by oil-in-water method as carrier of donepezil for the preventive of Alzheimer’s disease by controlled release

Abstract: Alzheimer's disease (AD) is the most common cause of dementia. Patients are generally to forget taking pills because of memory loss or to skip medication due to side effects; that might stop the medication and affect the results of the treatment. In this study, we combine donepezil with hydroxyapatite (HAP-DPZ) to deliver by intramuscular (IM) injection, which may prevent from patient to skip the daily medication and keep the medicine at a constant level in the blood to achieve a constant release. HAP particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The subsequent anchorage and growth of bone tissue on the cementline is also accelerated by the availability of the growth factors on the healing site [ 5 ]. Specifically synthesized hydroxyapatite was studied for drug loading and delivery [ 32 ]. It was shown that layered structures prepared such as TiO 2 /fluoro-hydroxyapatite/hydroxyapatite increased osteoblast cell proliferation in-vitro for orthopedic and dental implantation [ 33 ], and efforts existed to fabricate coatings for controlled drug delivery for faster healing and patient comfort, by sol-gel methods [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent anchorage and growth of bone tissue on the cementline is also accelerated by the availability of the growth factors on the healing site [ 5 ]. Specifically synthesized hydroxyapatite was studied for drug loading and delivery [ 32 ]. It was shown that layered structures prepared such as TiO 2 /fluoro-hydroxyapatite/hydroxyapatite increased osteoblast cell proliferation in-vitro for orthopedic and dental implantation [ 33 ], and efforts existed to fabricate coatings for controlled drug delivery for faster healing and patient comfort, by sol-gel methods [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this latter case, the doping of HA with divalent and trivalent Fe ions (FeHA) could be modulated to yield specific positioning of the two ions in the HA lattice and within the hydrated external layer, in turn, activating dipolar interactions and interplay generating intrinsic magnetisation properties. Considering the very good biocompatibility, bioresorbability, and osteogenic ability of such a magnetic apatite, in contrast with cytotoxic magnetic metal oxides, such a finding may open the opportunity for numerous applications in nanomedicine such as smart drug delivery system, magnetically guided nanoparticles for cell and gene therapy, and also in regenerative medicine to advance the osteogenic character of endogenous cells, particularly suitable in the case of patients with compromised endogenous abilities such as the elderly [ 55 , 56 ].…”
Section: Bioactive Ion-doped Nanohydroxyapatitesmentioning
confidence: 99%
“…Fang et al used porous hydroxyapatite synthesized by the oil-in-water method as the carrier of DP. They achieved the stable and sustained release of the drug through intramuscular injection . The design of Morris water maze experiment proved that it has a better improvement effect in the cognitive abilities of AD model animals.…”
Section: Routes Of Administration Of Donepezilmentioning
confidence: 99%